2008
DOI: 10.1103/physrevlett.100.165703
|View full text |Cite
|
Sign up to set email alerts
|

Combined Experimental and Theoretical Investigation of the Premartensitic Transition inNi2MnGa

Abstract: Ultraviolet-photoemission (UPS) measurements and supporting specific-heat, thermal-expansion, resistivity and magnetic-moment measurements are reported for the magnetic shape-memory alloy Ni2MnGa over the temperature range 100 K < T < 250 K. All measurements detect clear signatures of the premartensitic transition (TPM ∼ 247 K) and the martensitic transition (TM ∼ 196 K). Temperature-dependent UPS shows a dramatic depletion of states (pseudogap) at TPM located 0.3 eV below the Fermi energy. First-principles el… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

14
83
0
2

Year Published

2010
2010
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 117 publications
(99 citation statements)
references
References 34 publications
14
83
0
2
Order By: Relevance
“…26 These Fermi surfaces are contributed by nine bands that cross E F , resulting in a significant complexity of structure. Similar to the results reported by Opeil et al, 27 the highly symmetric Fermi surfaces are presented in the austenitic phase as well as majority-spin state in the martensitic phase, while a large Fermi surface reconstruction only occurs in the minority-spin band martensitic phase. These differences in Fermi surfaces are similar to these in the DOS shown in Fig.…”
Section: Resultssupporting
confidence: 89%
“…26 These Fermi surfaces are contributed by nine bands that cross E F , resulting in a significant complexity of structure. Similar to the results reported by Opeil et al, 27 the highly symmetric Fermi surfaces are presented in the austenitic phase as well as majority-spin state in the martensitic phase, while a large Fermi surface reconstruction only occurs in the minority-spin band martensitic phase. These differences in Fermi surfaces are similar to these in the DOS shown in Fig.…”
Section: Resultssupporting
confidence: 89%
“…Inelastic neutron scattering studies of the high-T cubic phase [9] showed a dramatic softening of the TA-2 phonon branch at q PM , indicative of a Kohn anomaly. These observations [9][10][11][12], together with the observed opening of a pseudogap at T PM [8,13], suggest an electronic instability within the Peierls scenario to be driving the PM-phase transition. The observation of a phase mode in the 10M phase [14] also suggested the electronic instability.…”
mentioning
confidence: 70%
“…Depending on the stoichiometry and the residual stress, the resulting low-T M phase is commonly found to have either tetragonal or orthorhombic symmetry, with a modulation period of ten (10M) or 14 (14M) atomic layers [6,7], respectively. For specific stoichiometries, e.g., Ni 2þx Mn 1−x Ga with x ≲ 0.1, a premartensitic phase (PM phase) is observed above T M [3] with the transition temperature T PM up to 50 K above T M [3,8]. In the PM phase, the lattice displays a harmonic threefold modulation with the wave vector q PM ¼ q max ð 1 3 ; 1 3 ; 0Þ.…”
mentioning
confidence: 99%
“…% of Cu and Co [12]. In addition, a premartensite exists above the martensitic transformation temperature and exhibits cubic structure with symmetry reduced by modulation with periodicity of six lattice planes (6M) [13]. The assumed phase sequence starting from high temperatures is then L2 1 ĺ6Mĺ10Mĺ14MĺNM during cooling [14].…”
Section: Introductionmentioning
confidence: 99%